Forecasting Population and Demographic Composition of Kuwait Until 2030 - Gulseven, Osman (International Journal of Economics and Financial Issues, 2016)
State of Kuwait is one of the richest countries in the world. Thanks to its oil reserves, the country hosts millions of foreign workers whose numbers have outpaced the Kuwaiti population. This article aims to forecast the future population of Kuwait using regional and nationality-gender based population data. Both linear and exponential population projections are used to obtain the most reliable estimates with the least forecasting error. Using the data between 1998 and 2015, I forecast the population of distinct administrative regions, expatriate and Kuwaiti population as well as the overall population of Kuwait. The results suggest that the population of Kuwait is likely to reach 5 million by 2020, and 7 million in 2030. The growth in expatriate population particularly male expat workers will dominate the population growth. It is recommended that state policies should consider such demographic and geographical imbalances in planning the future growth of Kuwait. Keywords: Population Forecasting, Demographics, Geographic Analysis, Linear Extrapolation, Exponential Extrapolation, Kuwait JEL Classifications: J10, J15